2023
DOI: 10.1186/s12905-023-02533-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of quality of life and mental health in breast cancer survivors in Northern Iran

Abstract: Background and purpose The global incidence of breast cancer is the highest among all cancers and is the primary reason for cancer-related fatalities. Our study aimed to assess the predictors of quality of life (QOL) and mental health in breast cancer survivors in Northern Iran. Methods This cross-sectional study was done on 96 female breast cancer survivors between the ages of 20 and 65 and was based on convenience samples. We gathered information… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Factors Associated with Health-Related Quality of Life Among Breast Cancer Survivors in Saudi Arabia: Cross-Sectional Study wellbeing. In chronic diseases such as cancer, quality of life involves not only physical health, but also a sense of wellbeing which encompasses their ability to do everyday tasks that are influenced by cancer and its treatment [7]. HRQOL has been extensively studied in western countries and found that BC survivors reported poor HRQOL with reduced physical and emotional function, and experienced major psychological symptoms relative to those without a cancer history.…”
Section: Introductionmentioning
confidence: 99%
“…Factors Associated with Health-Related Quality of Life Among Breast Cancer Survivors in Saudi Arabia: Cross-Sectional Study wellbeing. In chronic diseases such as cancer, quality of life involves not only physical health, but also a sense of wellbeing which encompasses their ability to do everyday tasks that are influenced by cancer and its treatment [7]. HRQOL has been extensively studied in western countries and found that BC survivors reported poor HRQOL with reduced physical and emotional function, and experienced major psychological symptoms relative to those without a cancer history.…”
Section: Introductionmentioning
confidence: 99%